Characterization of the cholinesterases present in head tissues of the estuarine fish Pomatoschistus microps: Application to biomonitoring - Monteiro, M.
In recent years biomarkers have been widely used for the assessment of effects and/or exposure to environmental contaminants. One of the most frequently used biomarkers is the inhibition of cholinesterases (ChE), which is a useful indicator of organophosphate and carbamate exposure and/or effects. Recent studies indicated that more than one ChE may be present in tissues of fish and that different forms may vary in their sensitivity to anticholinesterase agents. Cholinesterase activity of the juvenile of the common goby (Pomatoschistus microps), a widespread fish in estuaries of the Atlantic coast of northwestern Europe, was characterized using four substrates (acetylthiocholine iodide, acetyl-beta-metylthiocholine iodide, propionylthiocholine iodide, and S-butyrylthiocholine iodide) and three ChE inhibitors (eserine sulfate, BW284C51, and iso-OMPA) in different tissues of the fish head. In addition, the range of ChE activity that may be considered as "normal" for non-exposed P. microps was determined. The results suggest the presence of two types of ChE in the whole-head homogenate. The present study underscores the relevance of ChE characterization before its use as a biomarker in biomonitoring studies. (c) 2005 Elsevier Inc. All rights reserved.